PENGARUH SISTEM ZONASI PADA PENERIMAAN PESERTA DIDIK BARU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Aulia Muslimah Razak; Suarlin Suarlin; Andi Makkasau (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
This study aims to determine whether or not there is an influence of the zoning system on the learning motivation of students of SDN 002 Aralle. This type of research is classified as quantitative non-experimental research. The population in this study were students of SDN 002 Aralle with a total of 160 students and the sample used was students of SDN 002 Aralle. (slovin formula). The research method used in this study is to use non-experimental quantitative. The data collection technique used is to use a questionnaire with measurements using a likert scale. The data analysis techniques used are (1) Descriptive test (2) Normality Test (3) Hypothesis Test. The results of this study show that (1) The implementation of the zoning system for admission of new students at SDN 002 Aralle is in the moderate category (2) The level of learning motivation of students of SDN 002 Aralle is in the good category (3) The zoning system has a negative and significant effect on the learning motivation of students of SDN 002 Aralle